Plasticity of Anterior Pituitary Gonadotrope Cells Facilitates the Pre-Ovulatory LH Surge - Clay, Colin M.; Cherrington, Brian D.; Navratil, Amy M. (Frontiers in Endocrinology, 2021)
Gonadotropes cells located in the anterior pituitary gland are critical for reproductive fitness. A rapid surge in the serum concentration of luteinizing hormone (LH) secreted by anterior pituitary gonadotropes is essential for stimulating ovulation and is thus required for a successful pregnancy. To meet the requirements to mount the LH surge, gonadotrope cells display plasticity at the cellular, molecular and morphological level. First, gonadotrope cells heighten their sensitivity to an increasing frequency of hypothalamic GnRH pulses by dynamically elevating the expression of the GnRH receptor (GnRHR). Following ligand binding, GnRH initiates highly organized intracellular signaling cascades that ultimately promote the synthesis of LH and the trafficking of LH vesicles to the cell periphery. Lastly, gonadotrope cells display morphological plasticity, where there is directed mobilization of cytoskeletal processes towards vascular elements to facilitate rapid LH secretion into peripheral circulation. This mini review discusses the functional and organizational plasticity in gonadotrope cells including changes in sensitivity to GnRH, composition of the GnRHR signaling platform within the plasma membrane, and changes in cellular morphology. Ultimately, multimodal plasticity changes elicited by gonadotropes are critical for the generation of the LH surge, which is required for ovulation.